Arabic Pluriliteral Roots and Their Derivatives - Muftić, Teufik (Prilozi za orijentalnu filologiju, 2017)
U uvodnoj rijeÄi dat je kratak osvrt na korijene u arapskom jeziku i istaknuti osnovni zadaci rada. RazmatrajuÄ‡i dalje korijene od 4 radikala (korijenska suglasnika) tzv. kvadrilitere, iznesen je pregled osnovnih i izvedenih verbalnih i nominalnih formi ti Äetiri postojeÄ‡e vrste kod ovih korijena. U slijedeÄ‡em poglavlju opÅ¡irno su razmotreni naÄini nastajanja kvadrilitera i to kod njihovih glagolskih derivata. Na primjerima je pokazano da oni mogu nastati: 1) ponavljanjem bilitera (korijena od dva radikala); 2) afiksacijom trilitera (korijena od tri radikala); 3) ponavljanjem 3. radikala trletera; 4) denominativnom tvorbom; 5) izdvajanjem radikala iz. sloÅ¾enijih izraza; 6) premetanjem radikala kvadrilitera ili 7) njihovom meÄ‘usobnomzamjenom. Ti naÄini tvorbe razmotreni su potom kod imenskih oblika (imenica i pridjeva) najprije kod kvadrilitera, a onda kod kvinkvilitera (korijena od 5 radikala) koji nemaju glagolskih oblika. U kOraÄ‡em poglavlju govoreno je o nekim vaÅ¾nim pitanjima u vezi sa semantikom rijeÄi izvedenih iz plurilitera te znaÄaju prouÄavanjapojava u toj oblasti II vezi s nastajanjem ili gubljenjem pojedinih formi te promjenom znaÄenja tih rijeÄi pod uticajem raznih unutraÅ¡njih i vanjskih faktora, jeziÄke i vanjeziÄke prirode. U zavrÅ¡nom dijelu ukazano jena meÄ‘usobno djelovanje derivata svih korijena s ostalim rijeÄima u arapskom jeziku te na razloge arhaizacije ovih sloÅ¾enijih oblika i njihovog potiskivanja od strane formi bolje prilagoÄ‘enih potrebama Å¾ive rijeÄi. KonaÄno je upozoreno na nuÅ¾nost svestranijeg ispitivanja ovog dijela arapske leksike s obzirom na ulogu koju je on.a igrala u proÅ¡losti, ali je od znaÄaja i za savremeni jezik, kako u teoretskom smislu tako u izvjesnoj mjeri i na praktiÄnom planu, naroÄito, pak, u oblasti leksikografije, ali svakako i u ostalim podruÄjima savremene arabistike. ———————————————————— Arabic pluriliteral roots and their derivatives The brief introductory part deals with the problem of root in. Arabic in general, and with the basic objectives the present author set himself in the present paper, in accordance 'with the topic as .stated in the title. Closer consideration of the quadriliteral roots follows. First, a survey is given of the basic verb-forms and of the four types of the main deverbal forms. The following longer chapter consists of separate parts in which the ways in which quadriliterals are formed are discussed. These are: 1) reduplication of biliterals (i. e. roots with two radicals each); 2) affixation of the new radical on the triliterals (i. e. roots with three radicals); 3) reduplication 'of the third radical of the triliteral; 4) denominative formation of quadriliterals (in"verbs); 5) formation of quadriliterals from the elements of various syntagms (the so-called naht-contamination); 6) shifting (qalb - metathesis) of the radicals of the quadriliterals, and 7) mutual interchange (ibdiil) of radicals of quadriliterals. Then the ways of formation of new morphemes in the purely nominal forms (no'uns and adjectives) are discussed. These are numerous (as opposed to the few in the verbs) and the first systematist of the Arabic grammar, Sibawaih, whose data served as the basis for the study of all forms in the present paper has already observed this. That very material served as a basis for a short study of the basic and derived forms of quinquiliterals (roots with five radicals) in the next chapter. As is well-known those were just the nominal forms, since the verbs are not derived from those roots at all. Following these detailed etymological and morphological presentations, the paper deals briefly with the semantics of these words. In it, the importance 'of the study of semantic phenomena (synonymy, polysemy, antonymy, etc.) is indicated, as well as the Arabic vocabulary in thisÂ· domain, since they are important for the explanation of the creation and disappearance lo both the words themselves and the related meanings influenced by those linguistic and extra-linguistic factors which are constantly at work, changing both the linguistic forms and their semantic structures. In the final chapter the interaction of pluriliterals and their derivations and the same forms of the most numerous roots in Arabic, i. e. triliterals is presented briefly. By their numerousness, their phonetic and morphological characteristics, as well as their semantic structure, they push into the background the words derived from pluriliterals, that are often too long, oddsounding, obsolete, and even superfluous. However, regardless of the abovementioned, and of the fact that these forms have been neglected in the modern study of Arabic, it is necessary, for various reasons, to pay more attention to these forms that have played an important part in classical Arabic, and have continued to do so, up to a point, to this day. Their study also has a practical grammatical application, and especially in lexicography, in connection with the problem of order and distribution of lexical material in the dictionaries of Arabic for various purposes, as well as in connection with other problems in that area.